2015
DOI: 10.15274/inr-2014-10096
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of periprocedural hemodynamic changes in arteriovenous malformation vessels by endovascular dual-sensor guidewire

Abstract: Endovascular embolization is an important modality in the treatment of brain AVMs. Nowadays staged embolization is the method of choice for the prevention of perioperative hemorrhagic complications. Current theory suggests that simultaneous occlusion of more than 60% of AVM volume induces significant redistribution local blood flow. That, in turn, may lead to hemorrhage due to AVM rupture. Aside from angiographic findings, there is still no method that predicts the degree of safe par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…There was no intracranial dissection or perforation of vessels. The use of pressure wires had also been reported in case reports to assess the hemodynamics of cerebral aneurysms and arteriovenous malformation [27,28]. These case reports and our study suggested that with careful manipulation and the use of microcatheters and exchange maneuvers, if necessary, measurement of FF in even small intracranial vessels can be performed safely.…”
Section: Discussionsupporting
confidence: 72%
“…There was no intracranial dissection or perforation of vessels. The use of pressure wires had also been reported in case reports to assess the hemodynamics of cerebral aneurysms and arteriovenous malformation [27,28]. These case reports and our study suggested that with careful manipulation and the use of microcatheters and exchange maneuvers, if necessary, measurement of FF in even small intracranial vessels can be performed safely.…”
Section: Discussionsupporting
confidence: 72%
“…measured, but was not associated with hemorrhage of BAVMs, corroborating the findings of previous studies [10][11][12]. Future studies may investigate the potential use of transnidal time in determining the therapeutic effect of staged embolization for BAVMs [27,28]. Initial presentation of hemorrhage is consistently reported as a clinical feature associated with increased annual BAVM hemorrhage risk [29].…”
Section: Tablesupporting
confidence: 81%
“…In 1994, Miyasaka et al [30] demonstrated elevated pressure in drainage veins of 3 hemorrhagic BAVMs by measuring intravascular pressure intraoperatively. Nowadays, intraluminal flow velocity and pressure can be measured by using dual sensor guidewire during embolization for BAVMs [28]. Because of the advancements in imaging techniques, BAVM hemodynamics can be evaluated even before treatment, which may help in risk assessment for therapeutic decision making.…”
Section: Tablementioning
confidence: 99%
“…9 It was used in the neurovascular area in small case studies to assess the hemodynamic consequences of flow diversion for intracranial aneurysms 8,13 or of partial embolization of brain arteriovenous malformations. 10 However, its use in brain arterial structures is not in widespread clinical practice at present because of the risk of perforation and of thrombus formation, on one hand, and of the absence of clear clinical benefit resulting for such hemo- dynamic measurements, on the other hand. Navigation of the ComboWire in the dural sinuses appears to be safer than navigation in the cerebral arteries.…”
Section: Discussionmentioning
confidence: 99%